Modeling Informality Formally: Households and Firms - Sebastian Galiani; Federico Weinschelbaum (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2007)
Informality is widespread in most developing countries. In Latin America, 50 percent of salaried employees work informally. Three stylized facts characterize informality: 1) small firms tend to operate informally while large firms tend to operate formally; 2) unskilled workers tend to be informal while skilled ones have formal jobs; 3) Ceteris paribus, secondary workers are less likely to operate formally than primary workers. We develop a model that account for all these facts. In our model both heterogeneous firms and workers have preferences over the sector they operate and choose optimally whether to function formally or informally. There are two labor markets, one formal and the other informal, and both firms and workers act unconstrained in them. By contrast, a prominent feature of the pre-existing literature is the idea that worker's decisions play no role in determining the equilibrium of the economy. Using our model, we show that an increase in the participation of secondary workers would tend to raise the level of informality in the economy. This effect partially accounts for the increases in informality seen in Latin America over the past two decades.
Keywords: J2; J6; 330